Wolfram Syndrome: A Case Report and Review of Clinical Manifestations, Genetics Pathophysiology, and Potential Therapies - N. B. Toppings; J. M. McMillan; P. Y. B. Au; O. Suchowersky; L. E. Donovan (Case Reports in Endocrinology)
Background. Classical Wolfram syndrome (WS) is a rare autosomal recessive disorder caused by mutations in WFS1, a gene implicated in endoplasmic reticulum (ER) and mitochondrial function. WS is characterized by insulin-requiring diabetes mellitus and optic atrophy. A constellation of other features contributes to the acronym DIDMOAD (Diabetes Insipidus, Diabetes Mellitus, Optic Atrophy, and Deafness). This review seeks to raise awareness of this rare form of diabetes so that individuals with WS are identified and provided with appropriate care. Case. We describe a woman without risk factors for gestational or type 2 diabetes who presented with gestational diabetes (GDM) at the age of 39 years during her first and only pregnancy. Although she had optic atrophy since the age of 10 years, WS was not considered as her diagnosis until she presented with GDM. Biallelic mutations in WFS1 were identified, supporting a diagnosis of classical WS. Conclusions. The distinct natural history, complications, and differences in management reinforce the importance of distinguishing WS from other forms of diabetes. Recent advances in the genetics and pathophysiology of WS have led to promising new therapeutic considerations that may preserve β-cell function and slow progressive neurological decline. Insight into the pathophysiology of WS may also inform strategies for β-cell preservation for individuals with type 1 and 2 diabetes.